2012
DOI: 10.1111/j.1601-183x.2012.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

SEB‐3, a CRF receptor‐like GPCR, regulates locomotor activity states, stress responses and ethanol tolerance in Caenorhabditiselegans

Abstract: The CRF (corticotropin releasing factor) system is a key mediator of the stress response. Alterations in CRF signaling have been implicated in drug craving and ethanol consumption. The development of negative reinforcement via activation of brain stress systems has been proposed as a mechanism that contributes to alcohol dependence. Here we isolated a gain-of-function allele of seb-3, a CRF receptor-like GPCR in C. elegans, providing an in vivo model of a constitutively activated stress system. We also charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 72 publications
(99 reference statements)
5
72
1
Order By: Relevance
“…An ethanol-induced change in the activity of the BK channel gene underlies both ethanol tolerance and this ethanol-withdrawal hyperexcitability phenotype in flies (see "Synaptic Machinery and Ion Channel Genes"). Jee et al (2013) showed that C. elegans also exhibit alcohol-withdrawal hyperexcitability. After worms are exposed to 300-400 mM ethanol for three days, more than half of the exposed animals showed a tremor phenotype.…”
Section: Alcohol Dependence and Withdrawal Symptomsmentioning
confidence: 98%
See 1 more Smart Citation
“…An ethanol-induced change in the activity of the BK channel gene underlies both ethanol tolerance and this ethanol-withdrawal hyperexcitability phenotype in flies (see "Synaptic Machinery and Ion Channel Genes"). Jee et al (2013) showed that C. elegans also exhibit alcohol-withdrawal hyperexcitability. After worms are exposed to 300-400 mM ethanol for three days, more than half of the exposed animals showed a tremor phenotype.…”
Section: Alcohol Dependence and Withdrawal Symptomsmentioning
confidence: 98%
“…In addition, the C. elegans seb-3 gene, which encodes a CRF receptor-like GPCR that regulates arousal state and heat-shock stress responses, has also been implicated in ethanol responses. Comparison of seb-3 loss-of-function and gain-of-function mutants in worms showed that seb-3 promotes acute functional tolerance and withdrawal-induced tremors, whereas in mice, injection of a CRF-receptor antagonist delays and lowers the magnitude of acute functional tolerance (Jee et al, 2013).…”
Section: Gene and Behaviormentioning
confidence: 99%
“…The neuroprotective activities of the GLP-1 agonist liraglutide [2,3,35] are likely effective in C. elegans, since an orthologue of the human GLP-1R is present: seb-3 (C18B12.2), a CRF receptor-like G-protein-coupled receptor. Recent studies have shown that it is strongly involved in regulation of neuronal stress responses [36], however, its endogenous ligand is still unknown [37]. In contrast, neuroprotection by linagliptin is mediated independently of AKT1/FOXO signaling, since this effect was not abrogated in akt-1/daf-16 mutants.…”
mentioning
confidence: 95%
“…Mutations in multiple genes have previously been shown to generate altered phenotypes compared to wild-type animals upon treatment with ethanol (Davies et al 2003(Davies et al , 2004Kayser et al 2003;Kapfhamer et al 2008;Graham et al 2009;Speca et al 2010;Bettinger et al 2012;Bhandari et al 2012;Jee et al 2013;Raabe et al 2014). We examined two of these genes that have robust mutant ethanol response phenotypes, slo-1 and npr-1.…”
Section: Ehc Is Distinct From Previously Identified Ethanol Responsesmentioning
confidence: 99%